A Study on Trophic State in Lakes of Dong Da District, Hanoi - Thi The Nguyen, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 4, 2017)
One of approaches to assessing the water quality of lakes is to look at their primary production or trophic state. Protecting water quality of urban lakes from eutrophication is an important task of all governments. This study presents an analysis of the trophic state of lakes in Dong Da district, Hanoi. The tropic states of the lakes were characterized using the Carlson TSI and the Chlorophyll-a concentrations and referenced with the thresholds of US. The deviations of the Secchi depth and total phosphorus indices from the Chlorophyll-a index were used to identify limiting factors affecting to the tropic state of the lakes. It comes to a conclusion that most of the lakes in study area were hypereutrophic or eutrophic in August 2017 and eutrophic or oligotropic in March 2017. It also reveals that phosphorus was not a limited factor for algal biomass while other factors such as nitrogen showed certain effects. The time plot method suggested that transparency was dominated by non-algal factors such as color and size,of suspended substances/ particles, whereas the difference plot method revealed that large particles were dominated in the studied lakes. Consequently, further studies should be done to find out the real causes of the lakes’ eutrophication. Keywords Tropic state, lake, time pots, different pots References [1] U.S. EPA, National Lakes Assessment: A Collaborative Survey of the Nation’s Lakes, EPA 841-R-09-001, Washington, D.C, 2009. [2] Prasad, A. G. D. and Siddaraju, Carlson’s Trophic State Index for the assessment of trophic status of two Lakes in Mandya district, Advances in Applied Science Research 3 (5) (2012), 2992-2996. [3] Thomas R. Schueler, Urban Lake Management, Center for Watershed Protection, US, 2001. [4] Toronto and Region Remedial Action Plan, Preliminary Assessment of the Eutrophication or Undesirable Algae Beneficial Use Impairment (BUI) Along the Toronto and Region Waterfront, 2015. [5] Vollenweider, R.A. and J.J. Kerekes., Background and Summary Results of the OECD Cooperative Program on Eutrophication, In: Proceedings of an International Symposium on Inland Waters and Lake Restoration. U.S. Environmental Protection Agency. EPA 440/5-81-010 (1980), 26-36. [6] Rast, W. and G.F. Lee., Summary Analysis of the North American (US Portion) OECD Eutrophication Project: Nutrient Loading-Lake Response Relationship and Trophic State Indices, US EPA. Corvallis Environmental Research Laboratory. Corvallis, OR. EPA-600/3-78-008, 1987. [7] Carlson, Robert E., A trophic state index for lakes, Limnological Research Center, University of Minnesota, 1977. [8] Kratzer, C.R. and P.L. Brezonik, A Carlson-type trophic state index for nitrogen in Florida lakes, Water. Res. Bull. 17 (1981), 713-715. [9] Murthy, G.P., Shivalingaiah, Leelaja, B.C., Hosmani, S.P, Trophic State Index in Conservation of Lake Ecosystems, Proceedings of Taal2007: The 12th World lake Conference, 840-843. [10] U.S. EPA, Carlson's Trophic State Index. Aquatic Biodiversity, United States Environmental Protection Agency, 2007. http://www.epa.gov/bioindicators/aquatic/carlson.html accessed 17 February 2008. [11] Trophic State Equations, http://www.secchidipin.org/index.php/monitoring-methods/trophic-state-equations/ , accessed date: 20/8/2017. [12] Carlson, R.E., Expanding the trophic state concept to identify non-nutrient limited lakes and reservoirs, In Proceedings of a National Conference on Enhancing the States’ Lake Management Programs. Monitoring and Lake Impact Assessment. Chicago (1992), 59-71. [13] Carlson, R. E., Havens, K. E., Simple Graphical Methods for the Interpretation of Relationships Between Trophic State Variables, Lake and Reservoir Management, 21(1) (2005), 107-118, DOI: 10.1080/07438140509354418. [14] Carlson, R.E., Discussion on “Using differences among Carlson’s trophic state index values in regional water quality assessment,” by Richard A. Osgood. Wat. Res. Bull. 19 (1983), 307- 309. [15] Havens, K.E., H.J. Carrick, E.F. Lowe and M.F. Coveney, Contrasting relationships between nutrients, Chlorophyll a and Secchi transparency in two shallow subtropical lakes: Lakes Okeechobee and Apopka (Florida, USA), Lake and Reserv. Manage. 15 (2000), 298-309. [16] Dong Da People’s Committee, Water monitoring data in lakes of Dong Da district, 2017.